Multichronology of Harvey Nunatak, Napier Complex, East Antarctica - Takehara, Mami; Horie, Kenji; Hokada, Tomokazu (2022)
The 13th Symposium on Polar Science/Ordinary sessions [OG] Polar geosciences, Wed. 16 Nov. conference object